A Service-Oriented Architecture to enable virtual storage services: a dynamic collaboration context. (19th March 2009) - Chen, Shiping; Nepal, Surya; Chan, Jonathan; Moreland, David, John Zic
A dynamic collaboration, formed by business partners, requires self-contained, secure and reliable storage for sharing data among collaborating participants. As such this paper presents a virtual storage services architecture that utilises a Simple Distributed Storage Interface for virtualisation of different physical storage technologies and capabilities into a pool of logical storage for collaboration data. An e-health case study, with implementation and performance evaluation, shows the storage interface and architecture within the context of a Secure Storage Service, a key management service and a global backup service. The performance evaluation uses various experimental configurations and several commonly used data transport protocols.